WAW (web authoring wizard) - Breganza, Richie Paul; Corros, Ghia Marie; De Belen, Jocel; Viola, Irish Jocelyn (2001)
The World Wide Web has captured the public's interest like no other computer application or tool. In response, businesses have attempted to capitalize on the web's popularity. Organizations have used the web to publish many different types of information. The Web Authoring Wizard (or WAW) is a web-based application which starting businesses and small organizations may use for the main purpose of announcing their existence. WAW generates web pages for them after representatives from these groups have logged-on and have followed a series of steps for the creation of these web pages. This is a free software. Thus, upon completion of this project, it may be uploaded to the net and anybody can have access to it. Also, there is no provisions for redistribution.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Web sites -- Authoring programs; WAW (Computer program).